Flexural strengthening of concrete beams with CFRP laminates bonded into slits - Barros, Joaquim A. O. (2005)
Near surface mounted (NSM) strengthening technique using carbon fibre reinforced polymer (CFRP) laminate strips was applied for doubling the load carrying capacity of concrete beams failing in bending. This objective was attained and the deformational capacity of the strengthened beams was similar to the corresponding reference beams. The NSM technique has provided a significant increment of the load at serviceability limit state, as well as, the stiffness after concrete cracking. The maximum strain in the CFRP laminates has attained values between 62% and 91% of its ultimate strain. A numerical strategy was developed to simulate the deformational behaviour of RC beams strengthened by NSM technique. Not only the load carrying capacity of the tested beams was well predicted, but also the corresponding deflection.